The PROFILE OF ANTIBIOTIC USE IN PATIENTS WITH URINARY TRACT INFECTIONS AT ABDOER RAHEM GENERAL HOSPITAL, SITUBONDO - Hafiz Achmad Hafiz Auni Iswanto; SHINTA MAYASARI; Sholihatil Hidayati; Nur Hasanah (LPPM Universitas dr. Soebandi, 2025)
Harmful bacteria multiply, causing urinary tract infections (UTIs). Patients with urinary tract infections often receive antibiotics and supportive care. This study aims to assess the pharmacological treatment of patients with urinary tract infections at RSUD Abdoer Rahem Situbondo. This study used a descriptive design by collecting data retrospectively. This study used a sample of thirty medical records taken using total sampling from May to August 2024. The findings are presented in the form of tables and percentages. The results showed that RSUD Abdoer Rahem Situbondo used urinary tract infection drugs, with 90% of the pharmaceuticals included in the antibiotic class, and cefixime was the most commonly used antibiotic at 27.27%. Ondansetron was the dominant additional treatment, accounting for 21.5% of the total use of additional drugs, followed by ranitidine and lansoprazole at 16.07% and omeprazole and ketorolac at 14.29%.